Can and Should Social Workers Innovate? Two Case Studies of Hidden Social Innovation. - González , David; Puelles , Andoni (Journal of Social Work Education and Practice, 2023)
This paper advances the possibility of understanding social work as a hidden form of social innovation. This term has been developed in the last two decades in opposition to exclusively economic and technological innovation. Taking the ideas of von Hippel, George Mulgan, and others, you can define the innovation in Social Work as a specific one that tries to satisfy the urgent needs of the people. For this, two cases that could be understood as hidden social innovation from social work will be studied. Housing First project, developed in the United States in the late 1990s, will be analyzed. It is an innovation based on the complete rethinking of what a specific homeless subject requires, one that suffers from mental problems. In the second place Open until Dawn is a case of how to confront unemployed youth in a city in northern Spain. In this case, it was an NGO that developed a free time program with the participation of young people. As a conclusion, it will be understood that Social Work has been an innovative profession from a hidden social innovation point of view. It will be understood that this innovation is not something that has happened in recent years because of the economic crisis, but rather it has to do with its own nature.